STRATEGI AKSI SOSIAL DAN RESOLUSI KONFLIK UNTUK MEMBANGUN HARMONI BERAGAMA: STUDI PRAKTIK PENDIDIKAN ISLAM MODERAT DI KOTA MALANG - Fithrotul Fitri; Saeful Anam (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This article explores the role of interfaith collaboration in shaping social harmony through moderate Islamic education practices in Malang City, Indonesia. Focusing on the Forum for Religious Harmony (FKAUB), this qualitative case study investigates the strategic use of social action and conflict resolution to build religious harmony in a multicultural urban society. Drawing on data collected through in-depth interviews, field observations, and document analysis, the study reveals that FKAUB’s approach is grounded in inclusivity, active listening, and educational outreach. These strategies not only mitigate religious tensions but also foster long-term interfaith understanding. Findings show that religious moderation, when translated into concrete social actions, can be an effective model for peacebuilding. The study concludes that FKAUB’s initiatives represent a replicable model for other pluralistic communities seeking to navigate religious diversity through collaborative and educational means.